Efficient separation scheme for binary mixture of CO2 and H2S using aromatic components - Alnili, F.; Barifcani, Ahmed (Taylor & Francis Inc., 2017)
Separating a mixture of CO 2 and H 2 S into two products through distillation is both difficult and complicated because of similar relative volatility between the two gasses, particularly when a CO 2 concentration exceeds 80%. Therefore, the separation process can involve many separating stages. However, adding a solvent (agent) to the distillation column during the separation process makes this procedure easier. In this study, different solvents (ethylbenzene, o-xylene, m-xylene, and toluene) and operating conditions (temperature, pressure, and reflux ratio) for separating CO 2 from H 2 S have been simulated through distillation using Aspen HYSYS software. Furthermore, four different aromatic compounds (solvents) for different concentrations (from 0 to 40 mol%) have been evaluated to increase the CO 2 /H 2 S relative volatility, reducing the quantity of the solvent required and energy consumption. m-xylene was found to be the best solvent for separating CO 2 from H 2 S because of the significant effect on relative volatility, the low quantity required for high CO 2 recovery, and the low energy for generating the solvent.